THE EFFECT OF VOLUME VARIATION OF SILVER NANOPARTICLE SOLUTION TOWARDS THE POROSITY AND COMPRESSIVE STRENGTH OF MORTAR - W.S.B. Dwandaru; H.S.A Tina; A. Andreyani (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2016)
As the world is growing rapidly, people need better building materials such as mortar. The aim of this research is to determine the effect of adding silver nanoparticle solution towards the porosity and compressive strength of mortar. This research was started by making silver nanoparticle solution from nitrate silver (AgNO3). The solution is then characterized using Uv-Vis spectrophotometer. 5 mM silver nanoparticle is added in the process of mortar production with volume variation of the silver nanoparticle solution. The porosity, compressive strength, and the content of mortar were determined by digital scale, universal testing machine, and X-ray diffraction, respectively. For silver nanoparticle solution volumes of (in mL) 0, 5, 10, 15, 20, and 25 the porosity obtained are (in %) 20.38, 19.48, 19.42, 18.9, 17.8, and 17.5, respectively. The best increase in compressive strength is obtained for (in MPa) 29,068, 29,308, and 31,385, with nanoparticle solution volumes of (in mL) 5, 10, and 15 Keywords: mortar, silver nanoparticle, compressive strength